PELAKSANAAN ANALISA PELAPORAN MORTALITAS PASIEN RAWAT INAP DI PELAYANAN KESEHATAN RSUD Dr. M. ZEIN PAINAN - Dewi Mardiawati; Linda Handayuni; Engla Meisesdyanti (Ensiklopedia of Journal, 2023)
Mortality reports are a reference to see the number of death in hospital due to certain diseases. The current mortality report is still experiencing problems, namely the processing of reporting data is still manual, there is no determination of the cause of death code because there is no death certificate. This study aims to determine the analysis of the implementation of the mortality report at the hospital Dr. M. Zein Painan in 2021. Type of research is qualitative with a phenomenological approach. Data analysis using collaizi method.  Research was conducted by in-depth interviews with 4 informants, namely reporting officers, head of the medical record room, coder and death certificate issuance officers.  Results of the study indicate that the implementation of the mortality report has experienced problems including insufficient number of employees resulting in double jobs, staff knowledge is still minimal because they have never attended training, there are no policies, inadequate facilities and infrastructure and evaluation monitoring has not been carried out, thus affecting the output results. Implementation of mortality report has not been carried out completely because officers prioritize reports that have a direct impact on services. Therefore, it is necessary to recruit reporting officers, develop SIM RS for processing mortality data, make policies on mortality reports and evaluate the performance of officers on a regular basis.